2013
DOI: 10.1111/bju.12176
|View full text |Cite
|
Sign up to set email alerts
|

Manganese superoxide dismutase Ile58Thr, catalase C‐262T and myeloperoxidase G‐463A gene polymorphisms in patients with prostate cancer: relation to advanced and metastatic disease

Abstract: Objective• To evaluate the relationship between manganese superoxide dismutase (MnSOD) Ile58Thr, catalase (CAT) C-262T and myeloperoxidase (MPO) G-463A gene polymorphisms and the susceptibility and clinicopathological characteristics of prostate cancer. Patients and Methods• In all, 155 patients diagnosed with prostate cancer and 195 controls with negative digital rectal examinations and PSA levels of <4 ng/dL were enrolled in this study.• MnSOD, CAT and MPO gene polymorphisms were identified by polymerase cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 47 publications
(59 reference statements)
4
37
2
1
Order By: Relevance
“…In addition, Karunasinghe et al (2012) found a significant association between the C-262T allele and increased risk to PCa. In accordance with these results, Tefik et al (2013) found that CAT C-262T polymorphism is associated with increased risk to PCa. Interestingly, some studies have reported no association between CAT polymorphism and PCa (Choi et al, 2007;Ding et al, 2012).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In addition, Karunasinghe et al (2012) found a significant association between the C-262T allele and increased risk to PCa. In accordance with these results, Tefik et al (2013) found that CAT C-262T polymorphism is associated with increased risk to PCa. Interestingly, some studies have reported no association between CAT polymorphism and PCa (Choi et al, 2007;Ding et al, 2012).…”
Section: Discussionsupporting
confidence: 79%
“…The activity of CAT, which is an essential antioxidant, was found to be significantly diminished in PCa patients. There are conflicting results in the literature regarding the role of the CAT (C-262T) gene polymorphism in PCa (Choi et al, 2007;Battisti et al, 2011;Karunasinghe et al, 2012;Tefik et al, 2013;Geybels et al, 2015;Hu et al, 2015). Geybels et al (2015) suggested that CAT gene polymorphism is associated with stage III/IV prostate cancers.…”
Section: Discussionmentioning
confidence: 99%
“…At present we know that chronic exposure to excess ROS may contribute to brain damage and pathophysiology of schizophrenia [1,2,11,12], CAT involved in detoxification of ROS [5][6][7][8][9][10], and C-262T polymorphism is associated with CAT activity [3,4]. Taken together, these findings sufficiently provide us with a theoretical ration to investigate the association between CAT C-262T polymorphism and susceptibility to schizophrenia.…”
Section: Introductionmentioning
confidence: 86%
“…Several studies indicated that the polymorphism of C-262T CAT is associated with some multifactorial diseases [5][6][7][8][9][10]. At present we know that chronic exposure to excess ROS may contribute to brain damage and pathophysiology of schizophrenia [1,2,11,12], CAT involved in detoxification of ROS [5][6][7][8][9][10], and C-262T polymorphism is associated with CAT activity [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Одним из наиболее важных звеньев АОС является фермент каталаза, ген САТ которой локализован на 11-й хромосоме [14]. В нашем исследовании объектом изучения был выбран наименее описанный полиморфизм Т21А rs 17880664 гена САТ, при котором происходит замена азотисто-го основания тимина на аргинин в позиции 21 ну-клеотида, изученный в контексте предрасположен-ности к развитию некоторых соматических заболе-ваний [15,16]. Установлено, что у пациенток с невы-нашиванием беременности дикий аллель Т в гомози-готном состоянии выявлен в 40,98% (n=125), что до-стоверно не различалось от показателей в группе здоровых женщин -38,74% (n=74).…”
Section: результаты и обсуждениеunclassified